2021
DOI: 10.1108/jfp-02-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

“That’s the way my Wednesdays always go”: reverse-order instructions insufficient to mitigate schema-consistent errors in alibi generation

Abstract: Purpose The purpose of this study was to assess the ability of innocent suspects to produce accurate alibis, as well as to identify procedures police interviewers can use to increase the probability of generating accurate alibis. Design/methodology/approach In Study 1, 54 university students had a lecture (target event) end at either the normal time (schema group) or 25 min early (non-schema group) and then attempted to generate an alibi for the target event after either a short, moderate or long delay. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The authors reported that only about half of the information was consistent across the two alibi sessions. In several more recent studies, in which researchers could establish ground truth, participants often failed to provide alibis that were fully accurate (Cardenas et al , 2020; Eastwood et al , 2021; Laliberte et al , 2021; Leins and Charman, 2016). Not only are these sorts of ordinary mistakes likely to be viewed with scepticism, but they may also be viewed as a sign of deceit (Dysart and Strange, 2012).…”
Section: Alibi Generation and Corroborationmentioning
confidence: 99%
“…The authors reported that only about half of the information was consistent across the two alibi sessions. In several more recent studies, in which researchers could establish ground truth, participants often failed to provide alibis that were fully accurate (Cardenas et al , 2020; Eastwood et al , 2021; Laliberte et al , 2021; Leins and Charman, 2016). Not only are these sorts of ordinary mistakes likely to be viewed with scepticism, but they may also be viewed as a sign of deceit (Dysart and Strange, 2012).…”
Section: Alibi Generation and Corroborationmentioning
confidence: 99%